Ergothioneine as a Natural Antioxidant Against Oxidative Stress-Related Diseases - Fu, Tong-Tong; Shen, Liang (Frontiers in Pharmacology, 2022)
L-Ergothioneine (EGT) is a natural antioxidant derived from microorganisms, especially in edible mushrooms. EGT is found to be highly accumulated in tissues that are susceptible to oxidative damage, and it has attracted extensive attention due to its powerful antioxidant activity and the tight relationships of this natural product with various oxidative stress-related diseases. Herein, we 1) introduce the biological source and in vivo distribution of EGT; 2) review the currently available evidence concerning the relationships of EGT with diabetes, ischemia-reperfusion injury-related diseases like cardiovascular diseases and liver diseases, neurodegenerative diseases, and other diseases pathogenically associated with oxidative stress; 3) summarize the potential action mechanisms of EGT against these diseases; 4) discuss the advantages of EGT over other antioxidants; and 5) also propose several future research perspectives for EGT. These may help to promote the future application of this attractive natural antioxidant.